2018
DOI: 10.1186/s40478-018-0578-1
|View full text |Cite
|
Sign up to set email alerts
|

Membrane binding, internalization, and sorting of alpha-synuclein in the cell

Abstract: Alpha-synuclein (aSyn) plays a crucial role in Parkinson’s disease (PD) and other synucleinopathies, since it misfolds and accumulates in typical proteinaceous inclusions. While the function of aSyn is thought to be related to vesicle binding and trafficking, the precise molecular mechanisms linking aSyn with synucleinopathies are still obscure. aSyn can spread in a prion-like manner between interconnected neurons, contributing to the propagation of the pathology and to the progressive nature of synucleinopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 72 publications
3
78
0
1
Order By: Relevance
“…A similar hypothesis has been proved true in the case of intercellular transfer of tau amyloids through tunneling nanotubes, where extracellular tau species (monomers and fibrils) activated the formation of new nanotubes and therefore facilitated fibrillar tau transport between neurons (15). On the other hand, protein aggregates (tau and synuclein) are trafficked in early endosomes and lysosomes after the internalization (20,40,41). The need of the cell to deal quickly with a large amount of exogenous and potentially dangerous material might clog the degradation system, with subsequent impact on the normal turnover of the endogenous proteins.…”
Section: Discussionsupporting
confidence: 57%
“…A similar hypothesis has been proved true in the case of intercellular transfer of tau amyloids through tunneling nanotubes, where extracellular tau species (monomers and fibrils) activated the formation of new nanotubes and therefore facilitated fibrillar tau transport between neurons (15). On the other hand, protein aggregates (tau and synuclein) are trafficked in early endosomes and lysosomes after the internalization (20,40,41). The need of the cell to deal quickly with a large amount of exogenous and potentially dangerous material might clog the degradation system, with subsequent impact on the normal turnover of the endogenous proteins.…”
Section: Discussionsupporting
confidence: 57%
“…Cumulatively, the in vitro and cell culture experiments revealed that C-truncated ␣syn is primed to aggregate, which may be crucial in initial disease pathogenesis. Also, ␣syn fibrils are known to be trafficked to lysosomes in neurons (21,98), where these truncations are likely formed (22, 30 -34), and may play a role in initial fibril-induced propagation of pathology, as the C-truncated forms of ␣syn are much more readily induced to aggregate compared with FL ␣syn.…”
Section: Pathologic C-terminal Truncation Of ␣-Synucleinmentioning
confidence: 99%
“…Monomers readily passed through the membrane via diffusion while oligomers and fibrils can be taken up via dynamindependent endocytosis or macropinocytosis (Holmes et al 2013). Recent evidence suggests that membrane binding is a crucial step for a-Syn internalization, which is mediated by Rab proteins (Masaracchia et al 2018). A recent study characterizing the internalization mechanisms of a-Syn containing exosomes found that the process was an active as opposed to a passive process, yet resistant to conventional blockers of both clathrin and caveolin-mediated endocytosis as well as micropinocytosis (Delenclos et al 2017).…”
Section: Mechanisms Of A-syn Internalizationmentioning
confidence: 99%